Cost-effectiveness analysis of HIV/AIDS prevention among intravenous drug users in Iran's Drop-in Centers - Alireza Mirahmadizadeh; Reza Majdzadeh; Kazem Mohammad (Shiraz University of Medical Sciences, 2018)
Background: The goal of this study was to analyze the cost-effectiveness of harm reduction programs among Intravenous Drug Users (IDUs) who referred to Drop-In Centers (DICs) for prevention of Human Immunodeficiency Virus/Acquired Immune Deficiency Syndrome (HIV/AIDS) infection. Methods: To calculate the cost-effectiveness of HIV/AIDS prevention, we used data from a cross-sectional study carried out in 2009 in which we selected 13 DICs out of 45 active DICs using systematic random sampling. Through interview, data of all IDUs (1309) who had attended DICs were collected by means of a questionnaire approved by 3 experts. Averted cases of HIV infection were considered as the unit of effectiveness. The cost was also calculated from the perspective of governmental service provider and all costs were converted into US dollar (USD). Sensitivity analysis was used to measure the effect of some uncertain parameters in modeling the number of HIV cases that have been averted; also, Incremental Cost-Effectiveness Ratio (ICER) was estimated. Results: Results showed that the DICs averted around 120.2 HIV cases in one year (102.977 cases from drug injection, 11.45 cases from homosexual and 5.77 cases from heterosexual ways). ICER for each HIV infection averted was 13,248.5 USD. Sensitivity analysis showed that providing harm reduction services in the best and worst case scenarios could change the ICER from 13,055 to 13,954 USD for each HIV case averted, respectively. Conclusion: Since the most common cause of transmission and spread of HIV infection in Iran is drug injection via needle shared by IDUs, DICs programs in.